Wybór miejsca opodatkowania dochodu w aspekcie międzynarodowym - Klinowski, Marcin (The choice of income taxation place in international aspect, 2006)
Nowadays taxpayers more and more often take advantage of tax havens. The foregoing paper presents some criterion for the choice of income taxation place. The author takes under consideration, among other things, such factors like political stability, taxation system, banking system, foreign currency control, infrastructure etc.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 164-169